The Study of Two-Phase Flow for Crude Oil Production Using Computational Fluid Dynamics (CFD) - Ahmad Amirhilmi, A. Razak (2013)
Modeling the liquid-gas phase flow inside the horizontal and inclined pipe using CFD analysis is difficult due to continuously changing flow patterns. The main objectives of this research are to investigate the flow pattern of liquid-gas phase inside the horizontal and inclined pipe. Two-phase flows specifically on the liquidgas flow have a complex flow pattern that can be observed by develop the 3- Dimensional model using the Computational Fluid Dynamic (CFD) software that consist of Gambit for develop the model of horizontal and inclined pipe and then transfer the data to Fluent for further analysis. The simulation was conducted by modelling the horizontal and inclined plane with the length of 7 m and 0.08 m of inner diameter. This simulation was carried out under adiabatic condition and operating at normal temperature which was 298 K. The gravity was enabled in order to differentiate the phase flow inside the horizontal and incline pipe due to the density of liquid-gas phases. The simulation was run using the Volume of Fluid (VOF) for the solver. The manipulated variables which were velocity of the liquid and gas are been changed in order to predict the various flow pattern for both horizontal and inclined pipe. The results of flow pattern are been analyzed and compared with the previous researchers’ results. This can be concluded that all flow patterns appearing in the Baker chart can be simulated using existing CFD. In order to improve the effectiveness of the model developed, the simulation needed to be run until the iteration is converging.